Join the growing community of curious minds on IDNLearn.com. Our platform offers detailed and accurate responses from experts, helping you navigate any topic with confidence.

17.
Write the equation in standard form. Then factor the left side of the equation.

2x2 + 7x = 15


A. (2x – 5)(x + 3) = 0

B. (2x + 3)(x + 5) = 0

C. (2x – 3)(x + 5) = 0

D. (2x + 5)(x – 3) = 0


Sagot :

C (2x-3)(x+5). I just know. Please give me the brainliest

Answer:

C. (2x – 3)(x + 5) = 0

Step-by-step explanation:

The equation in standard form should be 2x^2 + 7x - 15 = 0

Factored the expression is (2x - 3)(x + 5).

In order to find the factored portion, you must look for factors of the front number (2) to use in the front of the parenthesis and factors of the last number (-15) to go in the end.  

When we use the ones that we have above, it distributes to the overall end result.  

(2x - 3)(x + 5)

2x^2 - 3x + 10x - 15

2x^2 + 7x - 15

View image Maddymcg408